Risiko Kredit, Likuiditas Dan Kecukupan Modal Terhadap Profitabilitas Berdampak Pada Return Saham - Sesilya Kempa (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
There are the problem of credit risk, liquidty risk and capital adequacy affecting the level of the bank performance. The study is aimed to find empirical evidence of the relationship of credit risk, liquidity risk and capital adequacy toward profitability and its impact to bank stock returns. This study uses causality approach with path analysis techniques to obtain results. The results showed that credit risk (NPL) has negative effect toward the profitability (ROA and ROE). While liquidity risk (LDR) has positive effect on ROA and capital adequacy (CAR) affects neghatively toward ROE. Furthermore, ROA negatively affects stock returns and ROE has positive effect on stock return.